Everyday Problem Solving in African Americans and European Americans With Alzheimer's Disease: An Exploratory Study - Ripich, Danielle N.; Fritsch, Thomas; Ziol, Elaine (International psychogeriatrics, 2002)
In this exploratory study, we compared the performance of 10 African American and 26 European American persons with early-to mid-stage Alzheimer's disease (AD) to 20 nondemented elderly (NE), using a shortened version of the Test of Problem Solving (TOPS). The TOPS measures verbal reasoning to solve everyday problems in five areas: explaining inferences, determining causes, answering negative why questions, determining solutions, and avoiding problems. Six linguistic measures were also examined: total utterances, abandoned utterances, length of utterances, maze words, questions, and total words. NE performed better than AD subjects on all but one measure of verbal reasoning ability. AD subjects also showed a trend to use more total utterances and abandoned utterances than NE. For the AD group, no ethnic differences were found for verbal reasoning or linguistic measures. The findings from this preliminary investigation suggest that, compared to European Americans, African American persons with AD demonstrate similar everyday problem solving and linguistic skills. Thus, assessments such as TOPS that examine everyday problem solving may be a useful nonbiased evaluation tool for persons with AD in these two ethnic groups.